Dynamics of human settlements ensuing from river transformation and changes in commercial behaviour: The birth of the "North-eastern Silk Road". (October 2016) - Rante, Rocco; Fouache, Eric; Mirzaakhmedov, Djamal
Abstract: This article focuses on the causes and dynamics of the origin of the caravan path linking Iranian cities to those of Central Asia from the northeast, to be more precise linking Nishapur and Merv to Bukhara and further to Samarkand, and thus overall linking Iran to China. It proposes to elucidate the causes and effects, which occurred after the appearance of what we could call the main arm of the Silk Road. After an analysis of the historical sources mentioning caravan routes crossing eastern Iran, Merv and Central Asia, this article presents the recent geo-archaeological results of the Archaeological Mission of the Bukhara Oasis (MAFOUB). Recent geomorphological discoveries have brought to light important morphological changes of the Zerafšan delta, to which are imputed major changes in human settlements and behaviours. By the 4th century BCE a huge human occupation of the oasis took place, which slightly later engendered a dynamic of massive urbanisation, rendering possible the connections between China and the Mediterranean Sea directly crossing the Bukhara Oasis. Highlights: Since the Last Glacial Maximum, the Zerafšan delta has modified its orientations from northwest to southwest. Since the Neolithic era, human occupation has settled at the ends of the Zerafšan delta. This arm of the Silk Road opened after the last Zerafšan delta change, in the 4th century BCE.